Visualizing Biodiversity with Voronoi Treemaps - Michael S. Horn; Matthew Tobiasz; Chia Shen (ISVD'09: Proceedings of the International Symposium on Voronoi Diagrams, 2009)
Introduced in 2005, the Voronoi treemap algorithm is an information visualization technique for displaying hierarchical data. Voronoi treemaps use weighted, centroidal Voronoi diagrams to create a nested tessellation of convex polygons. However, despite appealing qualities, few real world examples of Voronoi treemaps exist. In this paper, we present a multi-touch tabletop application called Involv that uses the Voronoi treemap algorithm to create an interactive visualization for the Encyclopedia of Life. Involv is the result of a year-long iterative development process and includes over 1.2 million named species organized in a nine-level hierarchy. Working in the domain of life sciences, we have encountered the need to display supplemental hierarchical data to augment information in the treemap. Thus we propose an extension of the Voronoi treemap algorithm that employs force-directed graph drawing techniques both to guide the construction of the treemap and to overlay a supplemental hierarchy.